Gambaran Kejadian Mola Hidatidosa Di Rumah Sakit Abdul Moeloek Provinsi Lampung - Rusmala Dewi (Jurnal Kesehatan Panca Bhakti Lampung, 2018)
Hydatidiform mole is an abnormal pregnancy characterized by cystic swelling of the corral veins accompanied by the trophoblast proliferation in several levels. Hydatidiform mole will be risk to develop into graveliness. The purpose of this research is to describe the occurrence of hydatidiform mole. The research design is descriptive. The data were taken from medical record of hydatidiform mole patients treated at RSAM Lampung Province in 2017. The results showed that the incidence of hydatidiform mole in RSAM Lampung Province in 2017 was 4.12% with the characteristics of age> 35 years of 54.05% and multipara by 40.54%. The results of this research is recommend to health workers to provide information to clients about the dangers of hydatidiform mole that should be anticipated by the client for re-visit to the hospital in order to evaluate the presence of malignancy after the evacuation of pregnancy.